The role of Si on microstructure and high-temperature oxidation of CoCr2FeNb0.5Ni high-entropy alloy coating. (June 2021) - Ma, Minyu; Han, Aihua; Zhang, Zunjun; Lian, Yong; Zhao, Chao; Zhang, Jin
Graphical abstract: Highlights: A novel high entropy alloys coating was successful manufactured by laser cladding. The influence of Si on Laves structure was investigated. The role of Si on inner oxidation zone of coating was carefully discussed. The oxidation mechanisms of high entropy alloys coating are revealed. Abstract: In this study, the CoCr2 FeNb0.5 Ni high-entropy alloys coatings with and without Si were prepared on Cr-Mo-V steel via laser cladding. The oxidation behaviors of the HEAs coatings in N2 -44CO2 -6H2 O gas at 800°C were systematically studied. Both coatings with and without Si consisted of FCC and Laves phases. Si atoms can be doped into Laves phase and improve the phase stability by reducing the spacing of crystal plane. The addition of Si improves the high temperature oxidation resistance since the (Cr, Si)Ox amorphous oxide layer can prevent oxygen from diffusing inward.